Akomodasi Bahasa di Napan, Nusa Tenggara Timur, Wilayah Perbatasan Indonesia-Timor Leste - Wati Kurniawati (Badan Pengembangan dan Pembinaan Bahasa, 2019)
Napan village is located in the Indonesia-Timor Leste border region whose people speak in Dawan and Indonesian. The problem in this studyare the accommodation of Dawan speakers, what is the direction of their accommodation between languages, and how do speakers’ who accommodate at the syntactic level based on gender and age groupThis study aims to identify the level of syntax used in language accommodation and its frequency based on the characteristics of respondents in Napan Village, the Indonesia-Timor Leste border region, East Nusa Tenggara. The method of the study is the survey method with 72 respondents of Dawan speakers which are divided into 36 men and 36 women as the samples. The results show that speakers of Dawan accommodate the language because of the security, familiarity, and growing trust within the speech participants. Speakers of Dawan are very positive about their language, positive about Indonesian language and quite positive about the languages of the neighboring country, namely Tetun Portu or Tetun Dili. Speakers of the Dawan language accommodate the Tetun Portu or Tetun Dili language at the lexical level, phrases, sentences, and expressions. Based on gender, female speakers of Dawan accommodate the Tetun Portu or Tetun Dili language (9.7%) more than male speakers (8.3%). Meanwhile, male speakers of Dawan (41.7%) are less accommodative to Tetun Portu or Tetun Dili than female speakers (40.3%). Based on age, speakers of Dawan who accommodate the Tetun Portu or Tetun Dili languages dominantly come from the ages of 26–50 years old (8.3%) compared to ages less than 25 years old (5.5%) and more than 51 years old (4, 2%). In addition, speakers of Dawan who do not accommodate the Tetun Portu or Tetun Dili languages are speakers older than 51 years old (29.2%) more dominant than those aged less than 25 years (27.8%) and those aged between 26-50 years (25%). ABSTRAKDesa Napan terletak di wilayah perbatasan Indonesia-Timor Leste yang masyarakatnya bertutur dalam bahasa Dawan dan bahasa Indonesia. Permasalahan dalam penelitian ini ialah mengapa penutur bahasa Dawan berakomodasi, bagaimana arah akomodasi antarbahasa, dan bagaimana penutur yang berakomodasi pada tataran sintaksis berdasarkan jenis kelamin dan kelompok usia? Penelitian ini bertujuan untuk mengidentifikasi tataran sintaksis yang digunakan dalam akomodasi bahasa dan frekuensinya berdasarkan karakteristik responden di Desa Napan, wilayah perbatasan Indonesia-Timor Leste, Nusa Tenggara Timur. Dalam penelitian ini digunakan metode survei. Sampel dalam penelitian ini adalah 72 responden penutur bahasa Dawan, yang terdiri atas 36 pria dan 36 wanita. Hasil penelitian menunjukkan bahwa penutur bahasa Dawan di Desa Napan berakomodasi karena kenyamanan, keakraban, dan untuk menumbuhkan rasa percaya mitra tutur. Penutur bahasa Dawan sangat positif terhadap daerahnya (bahasa Dawan), positif terhadap bahasa Indonesia, dan cukup positif terhadap bahasa negara tetangga, yaitu bahasa Tetun Portu atau Tetun Dili. Penutur bahasa Dawan berakomodasi terhadap bahasa Tetun Portu atau Tetun Dili pada tataran leksikal, frasa, kalimat, dan ungkapan. Berdasarkan jenis kelamin, penutur perempuan bahasa Dawan yang berakomodasi terhadap bahasa Tetun Portu atau Tetun Dili (9,7%) lebih dominan daripada laki-laki (8,3%). Sementara itu, penutur laki-laki bahasa Dawan yang tidak berakomodasi terhadap bahasa Tetun Portu atau Tetun Dili (41,7%) lebih dominan daripada perempuan (40,3%). Berdasarkan kelompok usia, penutur bahasa Dawan yang berakomodasi terhadap bahasa Tetun Portu atau Tetun Dili tampak dominan yang berusia 26—50 tahun (8,3%) dibandingkan dengan yang berusia <25 tahun (5,5%) dan > 51 tahun (4,2%). Di samping itu, penutur bahasa Dawan yang tidak berakomodasi bahasa adalah penutur yang berusia >51 tahun (29,2%) lebih dominan daripada yang berusia <25 tahun (27,8%) dan yang berusia 26—50 tahun (25%).